Synthesis and Characterization of Chitosan-HPMC-Methylparaben Hydrogel Film as an Antibacterial Wound Dressing Material - Endang Susilowati; Sulistyo Saputro; Lina Mahardiani; Nanik Dwi Nurhayati; Budi Hastuti; Wirawan Ciptonugroho; Dealories Qhurbasy Masyhuri; Ndiayu Ajeng Gareta; Izza Laila Nur Rohmah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Chitosan-HPMC-methylparaben hydrogel film has been successfully synthesized. Chitosan, a key component with desirable characteristics for the production of hydrogel films, has some shortcomings that can be overcome by adding HPMC, a commonly used gelling agent that improves the physical properties of hydrogel films, and methylparaben, which enhances mechanical properties and antibacterial activity. The physical properties test of the hydrogel film, i.e., the solubility and swelling test, showed that the addition of HPMC reduced the solubility ratio and increased the swelling ratio in the chitosan hydrogel film. The addition of methylparaben relatively increases the antibacterial activity, tensile strength, and elongation of chitosan-HPMC-methylparaben hydrogel films. The chitosan-HPMC-methylparaben dry film exhibits a tensile strength of 19.56 MPa and an elongation of 1.98%. Surface morphological characterization of the hydrogel film through SEM tests showed that the chitosan-HPMC-methylparaben hydrogel film has granules on its surface, whereas the chitosan-HPMC hydrogel film has a smooth texture with a flat surface. The addition of methylparaben reduces the degree of crystallinity and produces an amorphous phase. The chitosan-HPMC-methylparaben hydrogel film shows strong activity against S. aureus and E. coli. Based on these results, the hydrogel film can be considered an antibacterial material for wound dressings, although elongation still needs to be improved.